NUR AL-DIN AL-RANIRI’S SELECTED COMMENTARIES ON OTHER RELIGIONS IN THE 17TH CENTURY MALAY WORLD - Abdul Jalil, Mohd Noh; Alias, Majdan (Journal of Al-Tamaddun, 2020)
This article analyzes the contributions of Nur al-Din al-Raniri (d. 1658) to the discourse on religions other than Islam in the Malay world. Such discourse was not common during the early period of Islam in the region. Malay Muslim scholars at that time were focusing more on other discipline of knowledge in Islam. Despite the scarcity of such discourses, it was not totally abandoned. Three works by al-Raniri which contain discourses on religions other than Islam namely Tibyan fi Ma’rifat al-Adyan, Asrar al-Insan fi Ma’rifat al-Ruh wa al-Rahman and Bustan al-Salatin. Analysis on these texts are made to understand the priority he had at that time in making such discourses. Efforts made by al-Raniri in deliberating on religions other than Islam in his works proved that such discourse also exist during the early period of Islam in the Malay world. In fact, it was a continuation of similar discourse by Muslim scholars all over the world at that time.